#### Answer

$h^2+2ah-5h$

#### Work Step by Step

Given: $f(x)=x^2-5x+3$
and $f(a)=a^2-5a+3$
Now, we will have to solve.
$f(a+h)-f(a)=[(a+h)^2-5(a+h)+3]-(a^2-5a+3)$
This gives
$=a^2+h^2+2ah-5a-5h+3-a^2+5a-3$
or, $=h^2+2ah-5h$

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$h^2+2ah-5h$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.